Xyloglucan, Hibiscus and Propolis in the Management of Uncomplicated Lower Urinary Tract Infections: A Systematic Review and Meta-Analysis - Tommaso Cai; Umberto Anceschi; Irene Tamanini; Serena Migno; Michele Rizzo; Giovanni Liguori; Alejandro Garcia-Larrosa; Alessandro Palmieri; Paolo Verze; Vincenzo Mirone; Truls E. Bjerklund Johansen (MDPI AG, 2021)
Background: In the era of antibiotic resistance, an antibiotic-sparing approach presents an interesting alternative treatment of uncomplicated cystitis in women. Our aim is to perform a systematic review and meta-analysis to compare the effectiveness and safety profile of a medical device containing xyloglucan, hibiscus and propolis (XHP) in women with uncomplicated cystitis. Methods: Relevant databases were searched using methods recommended by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. The primary endpoint was clinical or microbiological success, defined as the complete (cure) and/or non-complete (improvement) resolution of symptoms at the end of treatment, or microbiological resolutions. Results: After screening 21 articles, three studies were included, recruiting a total of 178 patients. All three studies used placebo as comparator. A statistically significant difference was found in terms of clinical or microbiological resolution between the medical device and the comparator (3 RCTs, 178 patients, OR: 0.13; 95% CI: 0.05-0.33; p < 0.0001). No clinically significant adverse effects have been reported. Conclusion: A medical device containing xyloglucan, hibiscus and propolis is superior to comparator regimens in terms of clinical effectiveness in adult women with microbiologically confirmed or clinical suspicion of uncomplicated cystitis and is associated with a high patient compliance.